Peningkatan Minat Belajar Siswa Melalui Kegiatan Ranking 1 di Masa Pandemi Covid-19 - Turmudi Turmudi; Hayani Wulandari; Aprianto Abdurahman; Dini Febriani; Firda Fauziah; Intan Nurunnahar; Nunung Nurjanah; Nurhasanah Nurhasanah (Jurnal Pengabdian Masyarakat PGSD, 2021)
The development of technology nowadays became one of the opportunities that can be utilized well by the society especially in the world of education. However, some of the students were not utilized these technology development as well as possible, it makes their interest in learning decreased. The decrease of the students' interests especially during the school from home (online learning) became one of the reasons of the dedication team which is the PPLSP students of Universitas Pendidikan Indonesia, Purwakarta Campus at UPTD SDN 1 Cipaisan Purwakarta held a program that can increase the students' interest in learning especially the students in the elementary school level, the program called Ranking 1.  Ranking 1 is a competition program that be held via online using the Quizizz platform. Ranking 1 competition program, using the utility of the internet is necessary to increase students' interest in learning and improve students' awareness. The method that used in this dedication program is interactive quiz using IT Quizizz media. The result of this competition program became one of the efforts to increase students' interest in learning